An examination of how to engage migrants in the research process: building trust through an 'insider' perspective. Issue 2 (17th February 2022) - Ahmed, Ayesha; Vandrevala, T.; Hendy, J.; Kelly, C.; Ala, A.
ABSTRACT: Introduction: Ensuring all members of society can equally participate in research and the provision of services is a challenging goal. Increased migration has been mirrored by media narratives of social threat, leaving many migrants feeling differentiated and distrustful of mainstream society. Objectives: We explore how migrant and ethnic minority populations can be given the opportunity to participate in the research process. In this work, we iteratively and jointly developed a range of engagement strategies that adopt an 'insider' approach; seeking to eliminate feelings of differentiation and 'otherness' by establishing mutual trust. Design: Recruitment activities were carried out with 8 focus groups of first-generation South Asian migrants (the largest ethnic minority group in England). Our analysis was grounded in the broad principles of action research with reflective evaluation of our recruitment process using field observations and relevant focus group data; asking whether we tackled barriers to engagement. Results: Our findings show that 'otherness' can be reduced by establishing a trustworthy researcher-community relationship, but also that this relationship is complex, and needs to acknowledge residual mistrust. Alongside, researchers need to enable opportunities for empowered interaction, with flexible strategies to negotiate potential power divides. Conclusions : We can successfully create opportunities for engagement but there is no 'one size fits all'. Engagement requires tailored approaches that embrace flexibility, and position both engagement and non-engagement as positive and empowered choices.